A Critical Analysis of Lexical and Theological Errors in Rodwell’s Translation of Surah Al-Fatiha and Al-Baqarah: Implications for Quranic Translation Studies - Dr. Ghulam Mustafa; Muhammad Akram ul Haque; Khadeeja (Journal of Religion and Society, 2025)
This study critically examines lexical and theological errors in John Medows Rodwell’s 1861 translation of Surah Al-Fatiha and Al-Baqarah, highlighting the implications for Quranic translation studies. The analysis identifies systematic mistranslations, such as the rendering of Al-Raḥmān as "the compassionated" and Khalīfah as "vicegerent," which distort the Quran’s semantic and doctrinal messages. Employing a hybrid methodology of comparative textual analysis and error classification, the study reveals how Rodwell’s choices reflect 19th-century Orientalist biases, often reframing Islamic concepts through Christian theological lenses. Key findings include lexical inaccuracies (e.g., al-hamd as "Praise" instead of "All praise") and theological misrepresentations (e.g., anthropomorphizing Allah’s sovereignty). The study underscores the need for decolonial approaches in translation, prioritizing tafsīr-based semantics over Eurocentric equivalents. It also proposes an error typology framework to audit colonial-era translations, emphasizing the importance of linguistic precision and doctrinal fidelity in Quranic studies. Keywords: Quranic Translation, Rodwell, Lexical Errors, Theological Distortions, Orientalism, Decolonial Approaches, Tafsīr, Surah Al-Fatiha, Surah Al-Baqarah, Islamic Studies